A Review on Quantum Dot Light‐Emitting Diodes: From Materials to Applications. Issue 2 (16th November 2022) - Tian, Dadi; Ma, Haiguang; Huang, Guangguang; Gao, Min; Cai, Fensha; Fang, Yan; Li, Chenguang; Jiang, Xiaohong; Wang, Aqiang; Wang, Shujie; Du, Zuliang
Abstract: Quantum dot light‐emitting diodes (QLEDs), based on the solution‐processable colloidal quantum dots (QDs), are the high potential candidate for next generation display and lighting due to their high color purity, wide color gamut, low power consumption, and wide angle of view. Efforts have been made to improve the performance of the devices in order to achieve the goals of practical applications. This review focuses on the research progress in the materials and device physics of QLEDs, with the aims to accelerate the process of overcoming the obstacles to commercialization. Herein, the unique optical properties of QDs and the evolution of device structures are first reviewed. Then carrier dynamics, which has a decisive impact on device performance, is discussed in detail. In addition, the main obstacle to commercialization is emphasized as device stability, including operational stability, shelf stability, and efficiency roll‐off. Finally, unresolved issues in device physics are discussed, along with suggestions for future research directions. This review is expected to encourage further research in device physics and promote the development of QLEDs in the field of display and solid‐state lighting. Abstract : This review summarizes the research progress of quantum dot light‐emitting diodes (QLEDs), reviews the unique optical properties of quantum dots for light‐emitting applications, and the evolution of device structure. A summary of the recent progress of charge dynamics reveals that QLEDs have a different electroluminescence process compared to bulk semiconductor LEDs. Furthermore, solutions to the problems of stability are focused.